2009
DOI: 10.1007/s10620-009-1023-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Prophylactic Endoscopic Histoacryl Injection for Gastric Varices with a High Risk of Bleeding

Abstract: Prophylactic EHI can be a promising procedure for eradication of non-bleeding GVs in case with a high risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
5
21
0
Order By: Relevance
“…GOV1 was previously considered the most common type of gastric varices 14 , but, in our study, GOV2 was the most common type in both the younger and older patient groups (Table 2). This has also been reported in two other papers 45,46 . Recurrent bleeding may be attributed to severe liver disease and may lead to fatality.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…GOV1 was previously considered the most common type of gastric varices 14 , but, in our study, GOV2 was the most common type in both the younger and older patient groups (Table 2). This has also been reported in two other papers 45,46 . Recurrent bleeding may be attributed to severe liver disease and may lead to fatality.…”
Section: Discussionsupporting
confidence: 86%
“…Recurrent bleeding may be attributed to severe liver disease and may lead to fatality. Child-Pugh classification of B or C in cirrhotic patients was considered as one of the risk factors in recurrent gastric variceal bleeding between endoscopic treatment sessions 47 ; recurrent bleeding may also occur from incomplete obliterated varices after endoscopic therapy 9,36,46 . However, the early and late rebleeding had no significant difference between the two groups in our study, which may be due to the consistent quality in performing the gastric variceal obliteration by a single endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this is the example of isolated gastric varices type I provided by the authors, which shows that the fundal varices extended to the cardia. 25 In our study, rebleeding from GFV after treatment occurred in only 1 patient and was successfully treated with a second treatment. Of note, no patients with obliterated GFV on their first follow-up endoscopy had recurrence of bleeding from GFV.…”
Section: Discussionmentioning
confidence: 52%
“…In the past, a major contributor to poor patient outcomes was the lack of effective endoscopic therapies. However, injection of NBCA has now emerged as a first line therapy in the treatment of GV and may be effective in primary prophylaxis [5,6,8]. Tissue adhesive injection is not without risk however, and carries risks including embolization and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that NBCA injection is equally efficacious and associated with decreased morbidity when compared with transjugular intrahepatic portosystemic shunt (TIPS), a first line therapy for GV [7]. Studies have also shown NBCA injection may be effective as primary prophylaxis against GV bleeding [8]. Despite the growing evidence that NBCA injection is an effective treatment for bleeding GV, there remain concerns.…”
Section: Introductionmentioning
confidence: 99%